The Health Service System is Less Than Optimal Due to the Absence of Type A Hospitals in West Lampung Regency - Hafifatun Nuvus; Adi Kurnia Saputra; M Toi Yafi Maruf; Rizky Novaldi; Dimas Aldi Pratama; Abdul Halim (Penerbit Hellow Pustaka, 2025)
This article discusses in depth the problems of the health service system in West Lampung Regency which is still not running optimally. One of the main issues of concern is the absence of a Type A Hospital in the area, which has a significant impact on the limited medical facilities and quality of services available to the community. This study aims to identify factors that cause limited quality of health services, analyze the role of local governments in efforts to improve health services, and examine their impact on the welfare of the local community. The methods used in this study are site surveys and interviews. Site surveys were conducted at various health service facilities in West Lampung Regency to directly observe the condition of infrastructure, the availability of medical personnel, and other supporting facilities. In addition, in-depth interviews were conducted with health workers, community leaders, and local government officials to obtain further information regarding structural barriers and the role of policy in developing the health system. Through a political sociology approach, this article provides a critical analysis of the inequality of access to health services and its implications for social structure and community welfare. It is expected that the results of this study can provide real contributions in formulating strategic policies to improve and enhance health services in West Lampung Regency in a sustainable manner.